2012
DOI: 10.1021/ol301538s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functionalized Acenaphthenes and a New Class of Homooxacalixarenes

Abstract: The 5,6-dialkoxyethers of acenaphthene have been synthesized for the first time via modified Ullmann reaction conditions. Further modifications of the 5,6-dimethoxyacenaphthene allowed the synthesis of the first acenaphthene analogue of the octahomotetraoxacalixarenes. The X-ray structure of this new macrocycle and its complexation study with C(60) are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Calix[ n ]arenes are cyclic oligomers that have different sizes depending on the number of the repeated phenolic unit, ranging from 4 to 8 units [ 7 , 8 , 9 , 10 ]. This type of macrocyclic has a well-defined deep hydrophobic cavity surrounded by a hydrophobic upper rim and hydrophilic lower rim.…”
Section: Introductionmentioning
confidence: 99%
“…Calix[ n ]arenes are cyclic oligomers that have different sizes depending on the number of the repeated phenolic unit, ranging from 4 to 8 units [ 7 , 8 , 9 , 10 ]. This type of macrocyclic has a well-defined deep hydrophobic cavity surrounded by a hydrophobic upper rim and hydrophilic lower rim.…”
Section: Introductionmentioning
confidence: 99%
“…(Guo et al, 2018; Luo et al, 2018; Ma et al, 2018) have been widely used in host-guest chemistry, self-assembly materials, and biomedical field (Song and Yang, 2015; Alsbaiee et al, 2016; Li et al, 2017; Jie et al, 2018; Chen et al, 2019; Yang et al, 2019). Naphthalene-based macrocyclic arenes, termed as calixnaphthalenes, have also been produced (Poh et al, 1989; Andreetti et al, 1993; Shorthill et al, 2004; AlHujran et al, 2012; Avetta et al, 2012). However, calixnaphthalenes have not become highly popular receptors because they do not have unique molecular recognition properties.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 However, majority of such naphthalene-based molecular cavitand suffered from difficult regioisomeric products with ill-defined and shallow cavities, and scarcely displayed satisfactory guest binding. 23,24 To overcome these difficulties, recently Jiang et al 25−28 reported flexible naphthalene based macrocycles viz., oxatub[n]arene (n = 4, 5, and 6) and synthesized by the one-pot reaction under high dilution condition in which the repeating 2,6-dihydroxynaphthalene units are connected by ether (CH 2 −O−CH 2 ) linkage at the 1,5-positions, which minimize the potential isomerism and avoid the self-occupation of the cavity and also helps in maintaining the depth of cavities. Additionally, the flexible naphthalene moieties lead to multiple conformers which bring forth effective guest binding.…”
Section: ■ Introductionmentioning
confidence: 99%